Internet e cidadania: o estímulo ao debate político por meio do jornalismo fact-checking: um estudo de caso do projeto “Truco!” - Conceição, Desirèe Luíse Lopes (2018)
This dissertation aims to analyze the political information produced and disseminated by the digital platform “Truco!”, which is Agência Pública’s fact-checking project developed for the 2014 election in order to identify and ascertain the political debate taking place. The methodology adopted is based on the network policy concept of the author Manuel Castells, and consists of an elaboration for primary data collection, defined from the interactions and linked to the initial proposal of this research. The results recognize qualitative investigative journalism work with political participation activities, and it’s possible to relate them to the idea that the internet has elements to contribute to citizen education